INDEKS GLIKEMIK OYEK DAN TIWUL DARI UMBI GARUT (Marantha arundinaceae L.), SUWEG (Amorphallus campanullatus BI) dan SINGKONG (Manihot utillisima) - Verawati Hasan; Sussi Astuti; Susilawati Susilawati (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2011)
Tubers are believed to have functional properties because of their fiber (dietary fiber). Utilization of minor tubers like suweg and arrowroot as a raw material of oyek and tiwul is not yet widely applied. This study was aimed to indentfy glycemic index of oyek and tiwul made from arrowroot, suweg and cassava. The results showed that glycemic indexs of arrowroot , suweg and cassava oyek were 41, 42, and 30 respectively. While glycemic index of arroroot, suweg and cassava were 40, 40, and 29. These results indicates that oyek and tiwul from arrowroot, suweg and cassava can be classified as food that has low (<55) glycemic index.